TELAAH PASAL 338 -340 KUHP TENTANG PEMBUNUHAN BERENCANA (Analisis Pembunuhan Berencana Mahasiswa Universitas Surabaya Yang Di Masukkan Koper Lalu Dibuang oleh Guru Les Musik) - Gilang Herdila Wiratama; Mas Agus Priyambodo; Fatimah Ratna Wijayanthi (Jurnal Multidisiplin Dehasen (MUDE), 2023)
Some time ago, 22-year-old Angelina Natania, a University of Surabaya (Ubaya) student, became the victim of a murder. He was allegedly killed by Rochmat Bagus Apriyatna, who was his music tutor. However, there are other allegations that the perpetrator tried to control the victim's property. The victim's parents, Mr Bambang, said that the perpetrator deliberately approached his daughter to control his property. This allegation is based on the case of the loss of the vehicle registration certificate (STNK) for the victim's Xpander car. The formulation of the problem is as follows: How to study Article 338 of the Criminal Code and Article 340 regarding the determination of the offense of Murder in the Criminal Code? How can the judge decide on Article 340 of the Criminal Code regarding the offense of premeditated murder in the murder case of a University of Surabaya student? The type of research used in this study is normative legal research, which is a type of legal research obtained from literature studies, by analyzing a legal issue through laws and regulations, literature and other reference materials related to the Crime of Premeditated Murder.